Peningkatan Kesadaran Remaja Siswi SMPN 23 Padang Tentang Kesehatan Reproduksi dan Pencegahan Seks Bebas Melalui Edukasi Interaktif dan Media Visual: Enhancing Reproductive Health Knowledge and Preventing Risky Sexual Behaviors Among Female Adolescents at SMPN 23 Padang Through Interactive Visual-Based Education - Alfen Deza Pernadi; Anindira Nadiva; Dila Silvia; Aziva Dasver; Marceldo Aditya Melwin; Adisti Qamahadlina Larasati (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Adolescent reproductive health is essential for preventing risky sexual behaviors, particularly among female students who are at a vulnerable stage of psychosocial development. Preliminary observations at SMP Negeri 23 Padang revealed that reproductive health education had not been optimally implemented, as evidenced by limited educational resources, inactive student development forums, and insufficient reproductive health knowledge among female students. These conditions may increase adolescents' vulnerability to risky sexual behaviors. This community engagement program aimed to improve students’ reproductive health knowledge through the REPROFUN (*Reproductive Health Fun Class*) educational intervention. The program involved 83 female students from Grades VII to IX and employed a one-group pretest–posttest design. The intervention consisted of a pretest, interactive health education sessions, educational video presentations, behavior-based learning games, and a posttest to evaluate changes in participants’ knowledge. The results demonstrated a significant improvement in reproductive health knowledge, with the mean score increasing from 71.56 before the intervention to 94.93 after the intervention. The standard deviation decreased from 13.92 to 6.12, indicating a more consistent level of understanding among participants. In addition, advocacy activities successfully reactivated the Annisa Forum as a sustainable platform for reproductive health education and student development. Overall, the REPROFUN program proved effective in enhancing reproductive health knowledge through interactive visual-based education. This program offers a practical and sustainable model for school-based health promotion and the prevention of risky sexual behaviors among adolescents.